تاثير تدريبات القدرة القصوى باستخدام الاثقال في تطوير بعض القدرات البدنية الخاصة والبايوكينماتيكة والانجاز لرمي القرص للشباب - جابر, خالد خميس; صلال, محمد مجيد (Sulaimani Journal for Humanities, 2018)
Summary The maximum capacity is a relatively recent subject in the field of training. Therefore, the number of studies conducted in this field is still limited in comparison with the exercises of muscular strength. This is obviously an exercise for a combination of strength training and appliometry. And thus help to take out the largest possible amount of capacity and aimed to study the preparation of special training exercises maximum capacity using weights and the identification of these exercises in the development of some special physical abilities and Albuokinmatika and completion of the disk to throw me The researchers used the experimental approach to adapt the nature of the problem to the design of the experimental group. The field research procedures included explosive and rapid force tests and dynamic analysis procedures as well as testing the digital level of disc throwing. The researchers prepared the training curriculum. The training curriculum was started on December 25, 2016 and was completed on 24/2/2017, where training was conducted by three training units per week for a period of 8 weeks, ie a total of 24 within the period of special numbers, as the training intensity was determined according to the maximum achievement for weight training exercises in the training of members of the research sample, M weights up to 30-45% of the maximum exercise and performance at high speeds. The researchers concluded that there was a clear development in the level of rapid and explosive force and some biochemical variables for the members of the research sample. The training used in the training curriculum also had a clear effect on the development of the digital level of the research sample. The researchers recommend the need to train the maximum capacity and use other qualitative methods for what effect In the evolution of achievement.